THE ROLE OF NORTH LABUHANBATU BNN PR IN OVERCOMING NARCOTICS ABUSE IN PARPAUDANGAN VILLAGE - Abdul Mazid Siagian; Muhammad Alfikri (KABILAH : Journal of Social Community, 2022)
Abstract: This study aims to determine the Public Relations strategy of BNN North Labuhanbatu Regency in tackling Narcotics abuse in Parpaudangan Village. descriptive method with a qualitative approach This research was conducted at the BNN agency in North Labuhanbatu Regency which made Parpaudangan Village, Kualuh Hulu District, North Labuhanbatu Regency a target for cleaning up narcotics abuse. In this study, the informants were divided into two parts, namely key informants and supporting informants. Meanwhile, supporting informants such as the subdivision head. Data collection techniques used by researchers are observation, interviews and documentation. The data analysis technique used is data reduction, data presentation and conclusion. that the role of the North Labuhanbatu National Narcotics Agency in overcoming Narcotics abuse in Parpaudangan Village, especially in the field of prevention, is in accordance with the programs and activities owned by BNN Labuhanbatu Utara by looking at the facts on the ground. However, in its implementation there are still obstacles for BNN Labuhanbatu Utara in carrying out its programs and activities. Keywords: The Role of BNN Public Relations, Narcotics Abuse